ANALYSIS OF THE AVAILABILITY OF POSYANDU FACILITIES AND INFRASTRUCTURE AND ITS INFLUENCE ON PARTICIPATION OF HEALTH SERVICE TARGETS IN SUKADANA VILLAGE, TERARA DISTRICT, EAST LOMBOK REGENCY, WEST NUSA TENGGARA - Leni Lestari; Nurul Humairo; Sherina Fazirawati; Lalu Zahrul Basim (PT. Radja Intercontinental Publishing, 2026)
Posyandu (Integrated Health Post) is a form of Community-Based Health Effort (UKBM) that plays a crucial role in improving public health. The success of Posyandu activities is greatly influenced by the availability of adequate facilities and infrastructure and the active participation of the community as the target of health services. This study aims to analyze the availability of Posyandu facilities and infrastructure and their influence on the participation of health service targets in Sukadana Village, Terara District, East Lombok Regency. This study used descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. Informants consisted of Posyandu cadre leaders, cadres, and related parties who support the implementation of health services. The results showed that the main Posyandu facilities and infrastructure, such as baby scales, digital scales, and height measuring devices, were available and still suitable for use. However, there were still limitations in supporting facilities such as service tables and chairs. The availability of adequate facilities and infrastructure influenced the smooth running of health services and the level of community participation. The low participation of some targets was influenced by busy factors, health conditions, and limited time and mobility. Therefore, ongoing support from village governments and health workers is needed to improve the quality of facilities, the capacity of cadres, and community participation in integrated health post activities.